Full Potential GMAT Sentence Correction Intensive - Sapir, Bara (Nova Press, 2014)
Master Content. Upgrade your Mind. Elevate your Score!. * Includes Bonus TPNY Full Potential Handbook for test-day success. * 200+ detailed examples and valuable tips based on real GMAT questions. * Effective approaches for non-native speakers and different learning styles. * Fool-proof techniques for mastering each type of Sentence Correction question. * 30+ exercises for peak performance, drawn from sports psychology, mindfulness, and holistic health. With this book, you'll learn the Sentence Correction concepts and the critical thinking skills required to succeed on the verbal portion of th.